Pandangan orang tua mengenai intervensi aktivitas fisik dan diet pada siswa obesitas di sekolah dasar. - Rombemba, Finna R.; Rombot, Dina V.; Ratag, Gustaaf A. E. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2016)
Obesity is a global problem that taking place across the nations such as Spain (35% in children aged 6-9), Turkey (75% in elementary school children), and Canada (32% in children aged 5-17). The rate of obesity is increasing in Indonesia every year. According to Basic Health Research, overweight and obese children reached 18.8% in 2013. Obesity prevalence in North Sulawesi is 6.4% and 5.3% in Manado. This study aimed to find out parental views regarding physical activity and dietary intervention in obese students in primary schools. This research was conducted in three primary schools in the city of Manado. This study is descriptive study using mixed method. In the first part, quantitative research, we measured body weight and height to determine BMI and the student’s nutritional status. In the second part, qualitative research, we interviewed parents of the obese students. The prevalence of obesity in study schools is 20.9% in SD Garuda, 20.7% in SDN Winangun, and 18.7% in SD GMIM 20. Parents generally feel happy if their children are obese, even though they realize the consequences of obesity and acknowledge that a fat child is not as active and agile as children who are not obese. Parents agree at the idea of obesity interventions and states that obese children need a special program in order to reduce and maintain their weight; despite the fact that some parents put off the intervention program for their obese children.